Method for preparing polyolefin film by using volatile solvent

By using a mixing of volatile solvents and polyolefin resin and a twin-screw extrusion mechanism to prepare UHMWPE films, the problem of expensive equipment and difficult to adjust porosity in wet preparation technology is solved, and simplified process and high porosity film preparation are achieved. Comply with green environmental protection policies.

CN119189378APending Publication Date: 2024-12-27SHANGHAI RES INST OF CHEM IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411367461.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The wet preparation technology of existing UHMWPE films requires expensive equipment and complex steps, especially the extraction process increases production costs, and is difficult to adjust porosity, and does not comply with the policies of energy conservation, carbon reduction and green environmental protection.

Method used

The film is prepared by mixing volatile solvents with polyolefin resin through a twin-screw extruder and stretching process, avoiding the extraction step, and using the low dissolution temperature and low boiling point characteristics of the volatile solvent, the film is achieved with high porosity and green color. Environmentally friendly craftsmanship.

Benefits of technology

It reduces production costs, simplifies the process flow, and can adjust the porosity in the range of 40-85%. It is suitable for battery separators, water treatment, and breathable and moisture-permeable fabrics, with potential application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119189378A_ABST
    Figure CN119189378A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing a polyolefin film by using a volatile solvent, which comprises the following steps: (1) weighing polyolefin resin and a volatile organic solvent, stirring and fully mixing to obtain a uniform mixed solution; (2) feeding the obtained uniform mixed solution into a double-screw extruder to obtain a high-temperature melt, and carrying out curtain coating and cooling to obtain a membrane; and (3) stretching the obtained membrane to obtain a porous membrane, and carrying out heat setting to obtain a finished product membrane. Compared with the prior art, the method has the advantages that the solvent extraction process is reduced, the porosity of the membrane is adjustable in the range of 40-85%, the preparation process is green and environment-friendly, and the method has potential application in the fields of battery diaphragms, water treatment, breathable and moisture permeable fabrics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyolefin film preparation, and relates to a method for preparing a polyolefin film by using a volatile solvent. Background Art

[0002] The application range of polyolefin porous membranes, especially ultra-high molecular weight polyethylene (UHMWPE) porous membranes, is very wide. In recent years, with the annual growth of electric vehicle sales, the demand for lithium battery separators has greatly increased. At present, lithium battery separators are prepared by dry process using isotactic polypropylene as raw material and wet process using UHMWPE as raw material. UHMWPE separators melt at high temperatures without collapsing, have uniform pore size, and high mechanical strength, and occupy more than 70% of the market share in lithium batteries.

[0003] At present, the mainstream of UHMWPE diaphragms is to prepare them by wet process. For example, CN113972434A "A lithium battery diaphragm and its preparation method" of Zhongcai Lithium Membrane Co., Ltd. and CN113904059A "A high-pore uniform microporous membrane and its preparation method and battery" of Shanghai Enjie New Material Technology Co., Ltd. both propose to dissolve UHMWPE resin with white oil as solvent, and then remove the non-volatile white oil by synchronous or asynchronous biaxial stretching, and then use dichloromethane as extractant to form pores. The equipment required for producing UHMWPE diaphragms by wet process is expensive, and the steps are complicated and the production cost is high. Among them, extraction is the key to pore formation of diaphragms. In actual production, the white oil in the membrane is eluted by a large amount of dichloromethane. The eluted dichloromethane waste liquid contains about 5-15wt% of white oil. The dichloromethane in the membrane volatilizes into dichloromethane waste gas after entering the oven. Patent CN219307962U by Zhuang Zhi et al., "System for distilling dichloromethane by recycling waste heat using adsorption", etc., points out that dichloromethane waste liquid is recycled by fractionation treatment in a distillation tower; dichloromethane waste gas needs to be adsorbed by activated carbon fiber or granular carbon, and then steam heat adsorption and condensation recovery are performed to remove dichloromethane from the waste gas. These steps will increase production costs and are not in line with the current energy-saving, carbon-reduction and green environmental protection policies. At the same time, white oil will inhibit the growth of micropores (free volume holes) during the stretching process, making it difficult to adjust the porosity of the UHMWPE membrane. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a polyolefin membrane using a volatile solvent, which does not require the extraction step required by the UHMWPE membrane using a non-volatile solvent white oil in the prior art, facilitates the adjustment of porosity, reduces the process flow, and is green and environmentally friendly.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a polyolefin film using a volatile solvent comprises the following steps:

[0007] (1) Weighing a polyolefin resin and a volatile organic solvent, stirring and mixing them thoroughly to obtain a uniform mixed solution;

[0008] (2) feeding the obtained uniform mixed liquid into a twin-screw extruder to obtain a high-temperature melt, and then casting and cooling to obtain a film;

[0009] (3) The obtained membrane sheet is stretched to obtain a porous membrane without the need for an extraction step, and is heat-set to obtain a finished membrane.

[0010] Furthermore, the polyolefin resin is one or a combination of ultra-high molecular weight polyethylene polymerized by conventional magnesium-titanium based Ziegler-Natta catalyst, ultra-high molecular weight polyethylene with narrow molecular weight distribution synthesized by metallocene catalyst, ultra-high molecular weight polyethylene with bimodal molecular weight distribution, or ultra-high molecular weight polyethylene copolymerized with α-olefin.

[0011] Exemplarily, the molecular weight of the ultra-high molecular weight polyethylene is 800,000 to 4 million, and the molecular weight distribution is 2 to 8; the molecular weight of the narrow molecular weight distribution ultra-high molecular weight polyethylene is 800,000 to 4 million, and the molecular weight distribution is 1 to 4; the α-olefin is 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, etc.

[0012] Further, the volatile organic solvent is a solvent that can dissolve polyolefin resin and has a boiling point below 300° C. Further, the volatile organic solvent is one or a combination of toluene, xylene, n-nonane, n-decane, undecane, dodecane, kerosene, decahydronaphthalene, and tetrahydronaphthalene. More preferably, the organic solvent is xylene, tetrahydronaphthalene, decahydronaphthalene, and kerosene.

[0013] Furthermore, the mass ratio of the polyolefin resin to the volatile organic solvent is (5-50): (50-95).

[0014] Furthermore, in step (1), the polyolefin resin and the volatile organic solvent are stirred and mixed in a mixing kettle, the temperature in the mixing kettle is 80-120°C, and the ratio of the overflow port height d of the mixing kettle to the diameter D of the mixing kettle is set as the overflow parameter γ, wherein γ is 1 / 4-1 / 10, and the rotation speed of the mixing kettle is 180γrpm. The mixing kettle plays the role of mixing the resin and the solvent, preventing the resin from settling, and pre-swelling the resin. The mixing kettle and the twin-screw feeding port are sealed to prevent the solvent from volatilizing.

[0015] Furthermore, in the twin-screw extruder of step (2), the rotation speed is 20 to 80 rpm, the temperature zone in the middle part is 10 to 20° C. higher than the boiling point of the volatile organic solvent, the temperature of the rear end part and the temperature at the die head are 5 to 50° C. lower than the boiling point of the volatile organic solvent, and the slit width of the die head is 0.3 to 1.5 mm.

[0016] Furthermore, the melt film cast from the die slit undergoes thermally induced phase separation through cooling to form a film sheet, and the cooling method includes single-sided cold roller, double-sided cold roller, and water cooling.

[0017] Furthermore, the cooled film is wound up by a winder, and the thickness of the wound film can be regulated by the die slit or by the winding speed of the winder. The latter is more preferred in the present invention.

[0018] Furthermore, in step (3), the stretching is synchronous biaxial stretching or asynchronous biaxial stretching, the stretching ratio is 5 to 10 times, the stretching rate is 50 to 800 mm / min, and the transverse and longitudinal stretching rates are the same or different.

[0019] Furthermore, in step (3), the stretching temperature is 1 to 20° C. lower than the melting point of the stretched film.

[0020] In addition, the solvent in the film can be dried before stretching or directly stretched, and the solvent evaporates during the stretching process. Specifically, when the film is stretched after drying, the drying temperature is 30-90°C, and the evaporation of the solvent will cause the film to shrink. The film can be constrained around to prevent it from shrinking, or it can be allowed to shrink freely. The former is more preferred in the present invention.

[0021] Furthermore, the heat setting temperature is higher than the stretching temperature and lower than the melting point of the finished film. Specifically, the film shrinks during the heat setting process, and the shrinkage area is controlled to be 0-70%.

[0022] The present invention uses a volatile solvent to mix with a polyolefin resin. In this process, the resin can be prevented from settling at the feed port by using the overflow technology of the mixing kettle. The film cast by the die head passes through the water surface of the solvent liquid seal to cool and reel up, and then is dried. The dry film is heat stretched and heat-set. Compared with the prior art, the present invention has the following advantages:

[0023] 1) The dissolution temperature is lower, effectively avoiding the thermal degradation of the UHMWPE molecular chain;

[0024] 2) If additives (such as antioxidants and colorants) need to be added during the dissolution process, they will not be lost due to extraction (the additives lost in the wet process will be continuously enriched in the white oil during the distillation process);

[0025] 3) A large number of micropores generated by the evaporation of the solvent in the membrane grow larger and interconnected during the stretching process, and a high-porosity UHMWPE membrane can be obtained;

[0026] 4) Compared with the use of non-volatile solvents, this method reduces the solvent extraction process, the porosity of the membrane is adjustable in the range of 40-85%, the preparation process is green and environmentally friendly, and it will have potential uses in the fields of battery separators, water treatment, breathable and moisture-permeable fabrics, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the preparation process of a polyolefin membrane before casting;

[0028] Figure 2 is the morphology of the film prepared by volatile solvents;

[0029] Figure 3 This is the pore size distribution diagram of the UHMWPE membrane of comparative example 2;

[0030] Figure 4 This is the pore size distribution diagram of the UHMWPE membrane in Example 26. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0032] In the following examples, the ultra-high molecular weight polyethylene (UHMWPE) used was purchased from Shanghai Lianle Chemical Technology Co., Ltd., wherein the homopolymer resin (i.e., conventional resin) was LL-GM-1080 with a viscosity-average molecular weight of 1.2 million; the copolymer hexene resin was LL-LB-1080 with a viscosity-average molecular weight of 1.2 million, and the molar ratio of the copolymer components was 1‰.

[0033] The tensile strength test method is in accordance with GB / T 1040.3-2006. The specimen type is type II specimen, the specimen length is 150mm, the width is 15mm, the distance between the clamps is (100±5mm), and the tensile rate is (250±10)mm / min.

[0034] The porosity determination method is the national standard GB / T 36363-2018, and the porosity is calculated by the following two formulas:

[0035]

[0036] Among them, ρ1(g / cm 3 ) is the membrane surface density, m (g) is the membrane mass, L (cm) is the membrane length, b (cm) is the membrane width, ε (%) is the membrane porosity, d (μm) is the membrane thickness, ρ0 (g / cm 3 ) is the raw material density.

[0037] The aperture test method is the national standard GB / T 32361-2015, and the aperture is calculated by the following formula:

[0038]

[0039] Where D (μm) is the pore diameter, γ (mN / m) is the liquid surface tension, θ is the liquid contact angle, and p (Psi) is the gas pressure.

[0040] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0041] Part I Experiment: Preparation of Membranes

[0042] Comparative Example 1

[0043] See also Figure 1 The film process equipment shown includes a mixing kettle 1, a twin-screw extruder 3, a die head 3, etc., and an overflow port 2 is provided on the mixing kettle 1. Conventional UHMWPE (molecular weight 1.2 million, LL-GM-1080, 18wt%) and 50# white oil (82wt%) are accurately metered by a metering pump and then enter the mixing kettle for stirring (30°C). The overflow parameter γ is 1 / 6 and the rotation speed is 30rpm. The overflowed mixed liquid enters the twin-screw extruder, the screw temperature is 210°C, the die head temperature is 180°C, the screw speed is 60rpm, the cast film is cooled by a roller, the cooling roller temperature is 15°C, the film winding rate is 1.0m / min, the obtained film is extracted with dichloromethane, the film is fixed and dried all around, and the obtained film thickness is 0.59mm.

[0044] Example 1

[0045] Conventional UHMWPE (homopolymer, LL-GM-1080, molecular weight 1.2 million, 15wt%) and decalin (boiling point ~187°C, 85wt%) were accurately metered by a metering pump and then entered a mixing kettle for stirring (30rpm, 30°C), with an overflow parameter γ of 1 / 6 and a rotation speed of 30rpm. The overflowed mixed liquid entered a twin-screw extruder with a screw temperature of 210°C, a die temperature of 180°C, a screw speed of 60rpm, and the cast film was cooled by a roller, with a cooling roller temperature of 15°C and a film winding rate of 1.0m / min. The obtained film was dried at 50°C, and the film was fixed on all sides during the drying process. The obtained film thickness was 0.43mm.

[0046] Example 2

[0047] On the basis of Example 1, the mass fraction of UHMWPE was increased to 18 wt %, the other preparation parameters were the same, and the thickness of the obtained membrane was 0.46 mm.

[0048] Example 3

[0049] On the basis of Example 1, the mass fraction of UHMWPE was increased to 21 wt %, the other preparation parameters were the same, and the thickness of the obtained membrane was 0.54 mm.

[0050] Example 4

[0051] On the basis of Example 2, the solvent was replaced with kerosene, the screw temperature was 210° C., the die temperature was 180° C., and the other preparation parameters were the same. The obtained film had a thickness of 0.45 mm.

[0052] Example 5

[0053] On the basis of Example 2, the solvent was replaced with tetralin, the screw temperature was 210° C., the die temperature was 180° C., and the other preparation parameters were the same. The obtained film had a thickness of 0.45 mm.

[0054] Example 6

[0055] On the basis of Example 2, the solvent was replaced with dodecane, the screw temperature was 220° C., the die temperature was 190° C., and the other preparation parameters were the same. The obtained film had a thickness of 0.40 mm.

[0056] Example 7

[0057] On the basis of Example 2, the solvent was replaced with xylene, the screw temperature was 150°C, and the die temperature was 90°C. The screw temperature was too low and the viscosity was high, resulting in a large number of wrinkles on the membrane surface and failure to form.

[0058] Example 8

[0059] On the basis of Example 2, the diaphragm was formed by water cooling, the water temperature was controlled at 15° C. by a circulating refrigerator, and the other preparation parameters were the same. The thickness of the obtained diaphragm was 0.43 mm.

[0060] Example 9

[0061] On the basis of Example 8, UHMWPE resin (LL-LB-1080, molecular weight 1.2 million) of ethylene and hexene copolymer was used instead, wherein the molar ratio of α-hexene was 1‰, and the other preparation parameters were the same, and the obtained membrane thickness was 0.43 mm.

[0062] Example 10

[0063] Based on Example 9, the film winding rate was reduced to 0.5 m / min, and the other preparation parameters were the same. The obtained film thickness was 0.89 mm.

[0064] Embodiment 11

[0065] Based on Example 9, the film winding rate was increased to 1.3 m / min, and the other preparation parameters were the same. The obtained film thickness was 0.32 mm.

[0066] Experimental Part II: Stretching of the Diaphragm

[0067] Comparative Example 2

[0068] The film prepared in Comparative Example 1 was subjected to synchronous biaxial stretching, the stretching temperature was 120° C., the stretching ratio was 8×8 times, and the stretching rate was 800 mm / min. The properties of the finished film are summarized in Table 1.

[0069] Comparative Example 3

[0070] The film prepared in Comparative Example 1 was subjected to synchronous biaxial stretching, the stretching temperature was 110° C., the stretching ratio was 8×8 times, and the stretching rate was 800 mm / min. The properties of the finished film are summarized in Table 1.

[0071] Comparative Example 4

[0072] The film prepared in Comparative Example 1 was subjected to synchronous biaxial stretching, the stretching temperature was 130° C., the stretching ratio was 8×8 times, and the stretching rate was 800 mm / min. The properties of the finished film are summarized in Table 1.

[0073] Comparative Example 5

[0074] The film prepared in Comparative Example 1 was subjected to synchronous biaxial stretching, the stretching temperature was 120° C., the stretching ratio was 6×6 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0075] Example 12

[0076] On the basis of Example 1, the rolled film was not dried but directly subjected to synchronous biaxial stretching at a stretching temperature of 105° C., a stretching ratio of 8×8 times, and a stretching rate of 800 mm / min. The properties of the finished film are summarized in Table 1.

[0077] Embodiment 13

[0078] On the basis of Example 2, the rolled film was not dried but directly subjected to synchronous biaxial stretching at a stretching temperature of 105° C., a stretching ratio of 8×8 times, and a stretching rate of 800 mm / min. The properties of the finished film are summarized in Table 1.

[0079] Embodiment 14

[0080] On the basis of Example 3, the rolled film was not dried but directly subjected to synchronous biaxial stretching. The stretching temperature was 105° C., the stretching ratio was 8×8 times, and the stretching rate was 800 mm / min. The properties of the finished film are summarized in Table 1.

[0081] Embodiment 15

[0082] On the basis of Example 1, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film were summarized in Table 1.

[0083] Example 16

[0084] On the basis of Example 2, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0085] Embodiment 17

[0086] On the basis of Example 3, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120° C., the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0087] Embodiment 18

[0088] On the basis of Example 2, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 110° C., the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0089] Embodiment 19

[0090] On the basis of Example 2, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 130°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0091] Embodiment 20

[0092] On the basis of Example 2, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 140°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0093] Embodiment 21

[0094] On the basis of Example 2, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 6×6 times, the stretching rate was 800 mm / min, and the properties of the obtained film are summarized in Table 1.

[0095] Embodiment 22

[0096] On the basis of Example 4, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0097] Embodiment 23

[0098] On the basis of Example 5, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0099] Embodiment 24

[0100] On the basis of Example 6, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0101] Embodiment 25

[0102] On the basis of Example 8, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0103] Embodiment 26

[0104] On the basis of Example 9, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0105] Embodiment 27

[0106] Based on Example 10, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120° C., the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0107] Embodiment 28

[0108] Based on Example 11, the dried film was directly subjected to synchronous biaxial stretching, the stretching temperature was 120°C, the stretching ratio was 8×8 times, the stretching rate was 800 mm / min, and the properties of the finished film are summarized in Table 1.

[0109] Table 1 Performance parameters of biaxially stretched films

[0110]

[0111]

[0112] Examples 12-14 are direct stretching of the membrane. The solvent volatilization process will cause the membrane to shrink, resulting in a decrease in the air permeability of the UHMWPE membrane. The solvent causes the melting point of the membrane to decrease. The membrane can be stretched at 105°C. At the same time, the solvent orients the molecular chains during the stretching process, and the membrane has high strength. Examples 15-17 are volatile solvents that are dried and then stretched. The melting point of the membrane is about 135°C. The membrane can only be stretched to a higher multiple at a temperature close to the melting point. The solvent plasticizing effect is lacking during the stretching process, and the molecular chain orientation is difficult. The mechanical strength of the stretched membrane is poor, but the tiny holes (free volume holes) remaining after the solvent evaporates grow during the stretching process, and the porosity of the membrane is relatively high. Examples 18-21 are dry membranes stretched at different stretching temperatures and multiples. The higher the stretching temperature, the lower the permeability of the membrane, and the higher the mechanical properties; the larger the stretching multiple, the better the air permeability, but the thinner the membrane, the lower the porosity. Examples 22-24 use different volatile solvents. If the boiling point of the solvent is too high, the shrinkage rate of the membrane is large, which is not conducive to improving the performance of the membrane after stretching. If the boiling point of the solvent is too low, it is difficult to obtain a uniform and flat membrane. In addition, the price of the solvent is also a factor that must be considered. Example 25 uses water cooling, and the porosity of the membrane is improved compared to roller cooling. Example 26 is a copolymer of ethylene and α-hexene. The appropriate proportion of α-olefin copolymerization plays an important role in improving the mechanical strength of the membrane. Examples 27 and 28 are dry membranes obtained at different winding rates. The large number of pores remaining after the solvent evaporates will block the heat from transferring to the inside. Under the same stretching conditions, the thicker the membrane, the lower the internal temperature, and the internal molecular chain orientation is difficult, resulting in a decrease in the mechanical properties of the membrane.

[0113] Comparative Examples 2-5 use non-volatile solvent white oil, and the preparation process still requires the use of dichloromethane, which is cumbersome. At the same time, the adjustable range of porosity is small (<52%), and the processing process is sensitive to temperature. The membrane pores are easily closed as the temperature rises (the air permeability drops sharply), and the processing window is narrow. Figure 3 and Figure 4 The UHMWPE membranes prepared in Comparative Example 2 and Example 26 respectively show that the average pore size of the membrane prepared with volatile solvents is larger and the pore size distribution is wider. The larger and wider pore size also proves that the flux (air, Li + ) will be higher.

[0114] Part III Experiment: Heat Setting of Membranes

[0115] Embodiment 29

[0116] Based on Example 26, the stretched film was heat-set at a temperature of 130° C. for 5 min. Before heat-setting, the film was fixed on all sides to prevent shrinkage during the heat-setting process. The properties of the finished film are summarized in Table 2.

[0117] Embodiment 30

[0118] On the basis of Example 26, the heat setting temperature was 135°C for 5 min, and the film was fixed on all sides before heat setting to prevent shrinkage during the heat setting process. The properties of the finished film are summarized in Table 2.

[0119] Embodiment 31

[0120] On the basis of Example 26, the heat setting temperature was 140°C for 5 min, and the film was fixed on all sides before heat setting to prevent shrinkage during the heat setting process. The properties of the finished film are summarized in Table 2.

[0121] Embodiment 32

[0122] On the basis of Example 26, the heat setting temperature was 135°C for 5 minutes, and a 10% shrinkage area was left before the film was fixed on all sides before heat setting. The properties of the finished film are summarized in Table 2.

[0123] Embodiment 33

[0124] On the basis of Example 26, the heat setting temperature was 135°C for 5 minutes, and a 20% shrinkage area was left before the film was fixed on all sides before heat setting. The properties of the finished film are summarized in Table 2.

[0125] Table 2 Performance parameters of the film after heat setting

[0126]

[0127]

[0128] Heat setting helps eliminate the internal stress during the stretching process and improve the mechanical properties of the membrane. Examples 29-31 show that increasing the heat setting temperature helps improve the mechanical properties but reduces the air permeability, and Examples 32-33 show that the heat setting process causes the membrane to shrink to a certain extent, which helps improve the tear strength.

[0129] Figure 2 The morphology of the membrane prepared by volatile solvents is shown in Figure 1, where a is the membrane prepared in Example 9, and b shows the film stretched from the membrane in Example 26. It can be seen that the membrane prepared by the present invention has the same morphology structure as the membrane prepared by the existing wet process. In addition, the membrane prepared by the present invention has larger pores, which will be beneficial to the air and Li + It can be used in the separation field or lithium battery field.

[0130] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a polyolefin film using a volatile solvent, characterized in that: The following steps are involved: (1) Weighing a polyolefin resin and a volatile organic solvent, stirring and mixing them thoroughly to obtain a uniform mixed solution; (2) feeding the obtained uniform mixed liquid into a twin-screw extruder to obtain a high-temperature melt, and then casting and cooling to obtain a film; (3) The obtained membrane sheet is stretched to obtain a porous membrane, and then heat-set to obtain a finished membrane.

2. A method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: The polyolefin resin is one or a combination of ultra-high molecular weight polyethylene polymerized by conventional magnesium-titanium series Ziegler-Natta catalyst, ultra-high molecular weight polyethylene with narrow molecular weight distribution synthesized by metallocene catalyst, ultra-high molecular weight polyethylene with bimodal molecular weight distribution, or ultra-high molecular weight polyethylene copolymerized with α-olefin.

3. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: The volatile organic solvent is a solvent having a boiling point below 300° C. and capable of dissolving polyolefin resin.

4. A method for preparing a polyolefin film using a volatile solvent according to claim 3, characterized in that: The volatile organic solvent is one or a combination of toluene, xylene, n-nonane, n-decane, undecane, dodecane, kerosene, decahydronaphthalene and tetrahydronaphthalene.

5. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: The mass ratio of the polyolefin resin to the volatile organic solvent is (5-50): (50-95).

6. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: In step (1), the polyolefin resin and the volatile organic solvent are stirred and mixed in a mixing kettle, the temperature in the mixing kettle is 80-120° C., and the ratio of the overflow port height d of the mixing kettle to the diameter D of the mixing kettle is set as the overflow parameter γ, wherein γ is 1 / 4-1 / 10, and the rotation speed of the mixing kettle is 180γrpm.

7. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: In the twin-screw extruder of step (2), the rotation speed is 20 to 80 rpm, the temperature zone in the middle part is 10 to 20° C. higher than the boiling point of the volatile organic solvent, the temperature of the rear end part and the temperature at the die head are 5 to 50° C. lower than the boiling point of the volatile organic solvent, and the width of the die head slit is 0.3 to 1.5 mm.

8. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: In step (3), the stretching is synchronous biaxial stretching or asynchronous biaxial stretching, the stretching ratio is 5 to 10 times, the stretching rate is 50 to 800 mm / min, and the transverse and longitudinal stretching rates are the same or different.

9. A method for preparing a polyolefin film using a volatile solvent according to claim 8, characterized in that: In step (3), the stretching temperature is 1 to 20° C. lower than the melting point of the stretched film.

10. The method for preparing a polyolefin film using a volatile solvent according to claim 1, characterized in that: The heat setting temperature is higher than the stretching temperature and lower than the melting point of the finished film.

Citation Information

Cited By

  • Preparation method of polyolefin porous membrane and polyolefin porous membrane

    CN121133085A

  • Preparation method of polyolefin porous membrane and polyolefin porous membrane

    CN121224186A